Masks and the scourge of microplastic pollution - Menon, Anirudh K.; Mohan, Manu (International Journal Of Community Medicine And Public Health, 2023)
Personal protective equipment (PPE) has been the cornerstone of prevention of virus transmission during outbreaks like COVID-19.1 The recent pandemic necessitated the widespread use of masks among the public. While safe disposal of masks is satisfactorily achieved in hospital settings, the unsafe disposal of masks used in the households is a growing environmental concern. Also called as the ‘plastic impact of the pandemic’, the burden of face mask litter has grown into a significant pollution problem.